The Contribution of SMEs to Economic Growth in Africa - Oji, Chijioke Kennedy (My University, 2011)
In recent times, governments of countries and various internationally recognised institutions have come to the utter realisation of the somewhat overwhelming difference in the form of economic liberialisation and sustainable accelerated growth in development, which can be achieved through engaging the Small and Medium Enterprises (SMEs) in numerous sectors of the economy in different business operations. Targeting development through SME establishment has proved to be an important hydra-headed strategy to achieve an appreciable upgrade of the economic status of Western and Asian countries where SMEs account for about 20% of the Gross Domestic Product (GDP) and 40 – 60% of employment, through the complimentary ripple effects like poverty alleviation, job creation, market industralisation, crime reduction etc which all point toward an increased standard of living for citizens of the country. This however has not been the case for Africa. This study looks into the contributions of SMEs to economic growth in Africa as measured by selected economic variables i.e. entrepreneurial index of a country, per capita income of SMEs, trade statistics of SMEs, attraction of FDI for SMEs and capital investment in SMEs, all as contributors to the GDP of countries. GDP in this research is a measure of the economic position of a country. Five econometric models were developed for four African regions totaling 16 countries, using multiple regression analysis to investigate the relationship between GDP and the selected variables, in a bid to estimate the level of dependence of the GDP on these variables. The study finds evidence that GDP of selected African countries is not dependent on the economic indicators used as the yardstick for measurement. Hence, Africa shuts itself out of viable growth opportunities in deciding not to invest in the SME sector as a long-term strategy for economic resurgence and development. If the truly applaudable success achieved by foreign counterparts is to be realised on the African continent, in order to partake of the benefits of economic development, governments must invest capital and FDI in the form of education and management competencies within the SME sector and back this strategy up with favorable policies to foster sustainable economic growth and appreciable development
MBA - WBS
Keywords: Economic growth, Africa; Small businesses